Framing collaborative processes of digital transformation in cultural organisations: from literary archives to augmented reality. (3rd July 2020) - Arrigoni, Gabriella; Schofield, Tom; Trujillo Pisanty, Diego
ABSTRACT: At a time when it is particularly urgent to identify models of intersection across the digital and cultural sector to respond to an emergent funding and policy environment, this article contributes to a body of scholarly work around designing digital interventions for museums by identifying the role of cultural content in shaping design spaces for collaboration. The context of the article is a research project that brought together magical realist literature and the development of an Augmented Reality smartphone application realised through a public programme held at a museum of children's literature. This process created an open-ended design space within the organisation embedded into the development of public engagement workshops around magical realism and place making. It investigates how the cultural content (from archival material) occupied a key role in shaping technological development and suggests strategies that could grant autonomy and sustainability to cultural organisations in engaging in digital transformation.